DRY-ICE BLASTING AN OPTIMAL PANACEA FOR DEPURATING WELDING ROBOTS OF SLAG AND SPATTER (Journal of Technology and Operations Management, 2012)
Though MIG welding robots are extensively applied in the automotive assemblies ‘Spot Welding’ is the most common welding application found in the auto stamping assembly manufacturing. Every manufacturing process is subject to variations – with resistance welding, these include; part fit up, part thickness variations, misaligned electrodes, variations in coating materials or thickness, sealers, weld force variations, shunting, machine tooling degradation; and slag and spatter damage. All welding gun tips undergo wear; an elemental part of the process. Though adaptive resistance welding control automatically compensates to keep production and quality up to the levels needed as gun tips undergo wear so that the welds remain reliable; the system cannot compensate for deterioration caused by the slag and spatter on the part holding fixtures, sensors, and gun tips. To cleanse welding robots of slag and spatter, dry-ice blasting has proven to be an effective remedy. Presently, CO2 / dry ice blasting is being effectively used in a wide array of applications from heavy slag removal to delicate semiconductor and circuit board cleaning. This process can be used on-line without damaging equipment or requiring a machine "teardown". Unlike conventional toxic chemicals, high-pressure water blasting and abrasive grit blasting, CO2 / dry ice blasting uses dry ice particles in a high velocity air flow to remove contaminates from surfaces without the added costs and inconvenience of secondary waste treatment and disposal. This paper describes MIG and Spot welding process and analyses the slag and spatter formation during robotic welding of stamping assemblies; and concludes that the dry ice blasting process’s utility in cleansing of welding robots in auto stamping plant operations is paramount and exigent.